FISCAL SUSTAINABILITY AND FINANCIAL POTENTIAL OF A TERRITORIAL COMMUNITY: ESSENCE AND INTERCONNECTION (World of finance, 2025)
Вступ. У сучасних умовах глобальної нестабільності, наявності внутрішніх і зовнішніх загроз важливо досягти фінансової стабільності на рівні територіальних громад, адже вони забезпечують розвиток місцевого господарства та створюють умови для життєдіяльності населення кожної території. Для зміцнення економічної безпеки на місцевому рівні необхідне забезпечення фіскальної стійкості, яка досягається завдяки достатності фінансових ресурсів, що є основою фінансового потенціалу територіальної громади. Кризові явища та неможливість спрогнозувати динаміку розвитку економіки актуалізують необхідність перегляду наукових підходів до фіскальної стійкості та її впливу на фінансовий потенціал.Мета – ґрунтуючись на наукових підходах до визначення сутності понять “фінансовий потенціал” і “фіскальна стійкість”, дослідити їх взаємозв’язок у контексті посилення фінансового потенціалу територіальної громади.Результати. Досліджено основні підходи до визначення поняття “фінансовий потенціал територіальної громади”. Проаналізовано погляди вчених щодо впливу боргового навантаження на накопичення фінансових ресурсів громади. Здійснено порівняння фінансово-економічної сутності фіскальної стійкості та фінансової стабільності. Акцентовано на різнопланових підходах щодо наслідків зростання боргового навантаження для фіскальної стійкості бюджету. Обґрунтовано взаємозв’язок між фіскальною стійкістю та фінансовим потенціалом територіальної громади та сформульовано вектори впливу фіскальної стійкості на зміцнення фінансового потенціалу територіальної громади.Висновки. Узагальнення наукових підходів дало змогу з’ясувати, що основою фінансового потенціалу територіальної громади є фінансові ресурси. Виявлено, що сутність поняття фінансової стабільності є ширшим, ніж фіскальної стійкості, водночас спроможність забезпечувати достатній фінансовий ресурс для виконання обов’язків місцевою владою на довгостроковий період характеризує саме поняття фіскальної стійкості. Визначено вектори впливу фіскальної стійкості на фінансовий потенціал громади, а саме: фіскальна стійкість сприяє підтриманню фінансової стабільності і диверсифікації джерел доходів, підвищенню здатності залучати зовнішні ресурси, посиленню довіри жителів громади, мінімізації ризиків кризових ситуацій, розширенню можливостей для інвестицій. Introduction. In the current conditions of financial instability, internal and external threats, the financial condition of territorial communities is important, which provide support for the population of each territory and economic development. To strengthen economic security at the local level, it is necessary to ensure fiscal sustainability, which is achieved through the sufficiency of financial resources, which is the basis of the financial potential of the territorial community. Crisis phenomena and the inability to predict the dynamics of economic development actualize the need to revise scientific approaches to fiscal sustainability and its impact on financial potential.The purpose of the article is to explore their relationship in the context of strengthening the financial potential of the territorial community based on scientific approaches to defining the essence of the concepts of "financial potential" and "fiscal sustainability of the territorial community" based on scientific approaches to defining the essence of the concepts of "financial potential" and "fiscal sustainability of the territorial community".Results. The main approaches to defining the concept of “financial potential of a territorial community” are studied. The opinion of scientists on the influence of the debt burden on the accumulation of financial resources of a community is analyzed. The financial and economic essence of the concepts of “fiscal sustainability” and “financial stability” is compared. The versatility of approaches to the consequences of increasing the debt burden for the fiscal sustainability of the community budget is considered. The relationship between fiscal sustainability and the financial potential of a territorial community is substantiated and aspects of the influence of fiscal sustainability on strengthening the financial potential of a community are formulated.Conclusions. The generalization of scientific approaches allowed us to emphasize that the main component of the financial potential of a territorial community is financial resources. It was found that the essence of the concept of "financial stability" is broader in contrast to the term "fiscal sustainability", while the ability to provide sufficient financial resources to fulfill the duties of local authorities for a long period characterizes the concept of "fiscal sustainability". Aspects of the impact of fiscal sustainability on the financial potential of a community were identified, namely: fiscal sustainability contributes to maintaining financial stability; diversifying sources of income; increasing the ability to attract external resources; strengthening the trust of community residents; minimizing the risks of crisis situations; expanding investment opportunities.